WHAT FACTORS INFLUENCE THE DEVELOPMENT OF READING FLUENCY OF ROMA CHILDREN? THE EFFECTS OF WHOLE-CLASS REPEATED READINGS AND SCHOOL ABSENTEEISM - Dacian Dorin DOLEAN; Ioana TINCAS; Crina DAMSA (Studia Universitatis Babes-Bolyai, 2016)
Research literature shows that Roma children's literacy skills are less developed compared with their non-Roma peers. This situation represents a major deterrent in integration of Roma within the majority of countries of European Union. In this study we measured the effects of an intervention program aimed to diminish the gap in reading fluency skills between Roma and non-Roma 2nd grade children. The results indicated that a) Roma children's performance was significantly lower than their non-Roma peers before and after the intervention, b) there was no difference in the reading fluency growth rate of Roma and non-Roma children and c) poor school attendance of Roma children moderated the effect of Roma ethnicity. The findings suggest that poor school attendance has a particularly significant negative effect on the development of reading fluency of children of Roma ethnicity. Zusammenfasung. Die Forschungsliteratur zeigt, dass bei Roma-Kinder die Lese- und Schreibfähigkeiten weniger entwickelt sind im Vergleich zu ihren Nicht-Roma-Peers. Diese Situation stellt eine große abschreckende Wirkung auf die Integration der Roma in den meisten Ländern der Europäischen Union. In dieser Studie haben wir die Auswirkungen eines Interventionsprogramms gemessen, das darauf abzielt, die Lücke zwischen den Roma und Nicht-Roma-Kindern der 2. Klasse zu verringern. Die Ergebnisse zeigten dass, a) die Leistung den Roma-Kindern war signifikant niedriger als ihre Nicht-Roma-Kollegen vor und nach der Intervention, b) es gab keinen Unterschied in der Lesefluenz-Wachstumsrate von Roma und Nicht-Roma Kindern und c) schlechte Schulbesuch von Roma-Kindern moderiert die Wirkung von Roma-Herkunft. Die Ergebnisse deuten darauf hin, dass ein schlechter Schulbesuch einen besonders signifikanten negativen Effekt auf die Entwicklung der Lesefluenz von Kindern der Roma-Ethnizität hat. Schlüsselwörter: Roma; Leseflüssigkeit; Anwesenheit.